ONLINE STRATEGY OF PRINTED MEDIA COMPANY (Case Study of www.nirmalamagazine.com) - Veronica Sri Utami (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2018)
The sixth most popular online activities according to Yahoo TNS Net Index 2010 is reading news online. This behavior change will significantly affect conventional media business, including print media. The purpose of this research is to describe online strategy applied by Nirmala magazine. This magazine is one of the health magazines that secured significant readership on 2005, but somehow decreased its popularity in the following years. Nirmala magazine developed their own website at 2009, with the URL www.nirmalamagazine.com. It also established social media accounts and sent email blasts The print media company will certainly benefit from a strategy when they go online, which allows them to obtain the optimum benefit for the business. For this research, the author used qualitative methodology, predominantly case study technique. Interview, document review, and field observation are the methods used to collect data. The results and data analysis led to the findings that Nirmala website, supported by social media account and email marketing program, are actually useful as the tools to support their existing business. There are several functions served by this online form, among others, marketing communication function, medium to attract online advertisement, online brand building, customer service, and relationship building. Unfortunately, this website is not managed properly. Lack of understanding about optimum benefit from online side, poor decision about target market, budget, infrastructure, strategy and online management team, and also lack of synergy with all business units are some weaknesses that require improvement.